Multiscale micromechanics modeling of viscoelastic natural plant fibers - Li, Jie; Wang, Jian; Wang, Miao; Tie, Jinxin; Gao, Xuefeng; Wu, Yujie; Song, Jinhua; Xia, Chen (Frontiers in Materials, 2024)
Natural plant fibers are hierarchical structures with multi-level microstructures. With advances in composite material science, these fibers have been widely used in various polymer products. Therefore, it is crucial to quantitatively understand the relationship between their microstructures and mechanical behavior. This paper utilizes the Mori-Tanaka micromechanics model, viscoelasticity theory, and Zakian’s inversion method to study the impact of plant fiber microstructure on the viscoelastic behavior of multiscale structures. At the microscopic scale, the macromolecular polymer (matrix) and cellulose (fiber) are first homogenized. The second homogenization involves the cell wall microstructure, and the third homogenization considers the porosity of the cell wall and lumen to predict the effective modulus of fiber bundles. By applying the principle of elastic-viscoelastic correspondence, the viscoelastic mechanical parameters of plant fibers are calculated. The study examines the effects of cellulose crystallinity and lumen porosity on the structural stiffness and viscoelastic properties of fibers, identifying these factors as key influences on the mechanical behavior of plant fibers. Given their significant economic potential, the feasibility of using tobacco plant fibers as bio-based materials is also explored.